Analisis Kinerja Perusahaan Menggunakan Balanced Scorecard : Studi Kasus pada PT Qirindo Tekhnik Mandiri Kota Jakarta Barat - Siti Aisyah; Wati Rosmawati; Shofia Arsy (Universitas Veteran Bangun Nusantara, 2025)
This study aims to analyze the performance of PT Qirindo Tekhnik Mandiri by applying the Balanced Scorecard approach after the fire incident that disrupted business operations in early 2025. Balanced Scorecard was chosen because it provides a comprehensive measurement framework that evaluates performance through four perspectives: financial, customer, internal business process, and learning and growth. This research employed a descriptive method with both qualitative and quantitative approaches. Primary data were obtained through semi-structured interviews with the President Director, while secondary data were derived from financial statements from 2021 to 2024. The findings indicate that the company showed an improvement in financial performance in 2023, followed by a decline in 2024 due to operational disruption and increased costs. The fire incident also caused revenue decline and asset losses at the beginning of 2025, although the company succeeded in maintaining cash flow by implementing emergency funding strategies and cost adjustments. From the customer perspective, trust and loyalty remained stable due to transparent communication and service enhancements. Internal business processes demonstrated improvements in operational standards and the adoption of digital systems. In the learning and growth perspective, employee training and capacity strengthening activities were consistently carried out to support operational recovery. Overall, the Balanced Scorecard helped provide a clear performance evaluation and guide strategic recovery efforts post-crisis.